Respuesta :

Answer:

The answer to this question can be described as follows:

when x= 2. so, quotient value= 1.12

when x=-2.  so, quotient value= 0.04  

Step-by-step explanation:

Given:

[tex]\bold{\frac{x+1}{x(x-1)} \% \frac{4}{3}(x-1)} \\[/tex]

where,

[tex]x \neq 0, x\neq 1 , and \ x\neq -1[/tex]

In the given question the value of x is not equal to 1, 0, and -1. so, we put the value x= 2 in the above equation:

when x= 2

[tex]\Rightarrow \frac{2+1}{2(2-1)} \% \frac{4}{3}(2-1)\\\\\Rightarrow \frac{3}{2(1)} \% \frac{4}{3}(1)\\\\\Rightarrow \frac{3}{2} \% \frac{4}{3}\\\\\Rightarrow 1.5 \% 1.33\\\\\Rightarrow \boxed{1.12}[/tex]

when we put the value x= -2. it will give:

[tex]\Rightarrow \frac{-2+1}{-2(-2-1)}\ \% \frac{4}{3}(-2-1)\\\\\Rightarrow \frac{-1}{-2(-3)} \ \% \frac{4}{3}(-3)\\\\\Rightarrow \frac{-1}{6} \ \% -4 \\\\\Rightarrow -0.16\ \% -4 \\\\ \Rightarrow \boxed{0.04}[/tex]

Answer

The correct answer is B on ED 2021 Trust Me

Step-by-step explanation: